Fermentation Technology Is Utilized To Generate Efficient Organic Fertilizers, Specifically Bokashi - Mazekea Madginea; Shoelooti Skalat (Akademi Sertifikasi Profesi Internasional, 2024)
The aim is to provide farmers with training and skills to efficiently utilize natural environmental resources, with particular emphasis on the optimal use of domestic vegetable and fruit waste. This will entail utilizing fermentation technology, which is predominantly unfamiliar yet desired by the community, to convert trash into more advantageous and environmentally friendly goods through the use of effective native microbes. Presently, folks exhibit less interest in investigating alternative approaches for the utilization of waste, especially home organic refuse. Bokashi fertilizer is an organic fertilizer created via the fermentation of organic waste, including manure and compost, employing decomposing microorganisms such as fermentative fungi or bacteria. The outcome is a granular, solid fertilizer enriched with a diverse array of nutrients, both macronutrients and micronutrients, readily absorbed by plant roots. The aim of this bokashi fertilizer course is to instruct and empower the community in the processing of organic materials sourced from household waste. The course intends to propagate fermentation technology for the management of organic waste in the community. This course seeks to enable farmers, vital societal contributors, to adopt innovative solutions for addressing environmental challenges. The methodology involves training participants, facilitating participant-led practice and mentoring, and evaluating the entire activity. This link augments the agricultural community's expertise and proficiency in employing domestic organic waste. The analysis of the questionnaire data indicated that all participants acknowledged the benefits of this training exercise. They have enhanced their interest and gained more profound information, and they are ready to apply it in their daily life